Menjadi Guru yang Inovatif dan Kreatif di Era Digital: Seminar pada Sekolah Dasar Negeri 4 Halong Ambon - Binnendyk, Sophia; Hukom, Salmon James; Lewier, Christian Albert (Universitas Pattimura, 2025)
The “This Community Service activity aims to provide additional information and knowledge about the importance of being an innovative and creative teacher in today's digitalization era for elementary school teachers. This seminar is motivated by the demands of the times, where elementary school students have daily activities involving smartphones in playing games and other activities. In addition to the boredom characteristic of elementary school students, teachers are required to be more creative in developing innovative teaching materials and implementing them in the classroom by utilizing IT to overcome this challenge. The methods used in this training include lectures and interactive discussions. This activity was attended by 8 teachers at State Elementary School 4 Halong, Ambon City. The results of this seminar showed the participants' awareness of the importance of being innovative and creative teachers in developing teaching materials and in the teaching and learning process in the classroom. In addition, the critical questions asked by the participants during the discussion illustrated their better understanding of the seminar topic. This activity concludes that a seminar on becoming a professional teacher through the implementation of digitalization in education is needed for teachers.